Kreasi Kue Bolu Khas Desa Wisata Bonjeruk Berbahan Dasar Buah Endemik Lobe-Lobe Sebagai Oleh-oleh. - Sasmita, M Tanggap; Apriyanto, Yusup (JURNAL GASTRONOMI INDONESIA, 2025)
Bonjeruk Tourism Village, part of the Mandalika Super Priority Tourism Destination, has unique biodiversity, culture, and cuisine potential, including the distinctive Lobe-Lobe fruit. This research aims to develop a pound cake made from Lobe-Lobe fruit as a typical village souvenir to complement the existing culinary potential. The research uses the Borg & Gall research and development model, involving organoleptic tests by 5 experts and hedonic tests by 45 visitors to the tourist village aged between 16-60 years. The analysis requires documentation, organoleptic tests, and hedonic tests with a 5-point Likert scale. The results show that Cake Lobe-Lobe excels in taste (average score of 4.23) and texture (4.28), while aroma (4.10), color (4.15), and moisture (4.10) meet consumer preferences. The appearance aspect (3.97) requires further innovation. Future research recommendations include the development of product variations based on Lobe-Lobe, innovation in attractive appearance and packaging, and strengthening product promotion as a typical souvenir of Bonjeruk Tourism Village